Design and Analysis on Disposable Mouth Mirror - Shahriman Adenan, Mohd; Zaira Azlan, Mujahidah; B. Saedon, J.; M., Azuddin (International Journal of Engineering and Technology, 2018)
This paper presents on a conceptual design approach for developing design and simulation analysis on dental toolkit for disposable mouth mirror. Disposable mouth mirror designs contain with a very small and precise features for it handles and fix angle between shank and working area (mirror). To develop a 3D cad data, a conceptual design method in establishing disposable mouth mirror is carried out by using morphological chart and the best concept has been selected. A 3D cad model of disposable mouth mirror has been construct by using CATIA V5 based on the best criteria. The simulation and analysis by moulding software package is used in order to determine its suitable gate location, runner system, sprue, and fill time for single and double cavity. Material used for this product has been selected from plastic material polypropylene (PP) for its durability, light weight and low cost. At the end, a new innovative design of disposable mouth mirror including all ergonomics aspects and criteria has been designed and simulates to study its product behaviour.Â